Do armores sacale insects influence visit rate and feeding activity of ants on Echinopsis chilensis - Rios Aramayo, R.=700 1 Jimenez, M.
(Es, En)
Ilus., 3 ref.
Keywords: FORMICIDAE; HABITOS ALIMENTARIOS; SECRECIONES DE LAS PLANTAS; AZUCARES; CACTACEAE; CHILE; HORMIGAS; REVISTA CHILENA DE ENTOMOLOGIA